Metastatic choroidal melanoma in the breast: a case report and review of the literature - Loay Abudalu; Vinisha Malhotra; Nabila Nasir; Sami Titi (Journal of Pathology and Translational Medicine, 2023)
The breast is an unusual site for metastases, accounting for less than 2% of malignant breast lesions but include those from malignant melanomas, carcinomas, sarcomas, and lymphomas from various organs. We diagnosed a very rare case of metastatic choroidal melanoma for a 67-year-old female who presented with a right breast lump and who had been previously diagnosed with choroidal melanoma-monosomy 3 in 2017. To the best of our knowledge, only five such cases have been published so far, with one in a male patient.